Enhancing the performance of blown asphalt binder using waste EVA copolymer (WEVA) - A.M.M. Abd El-Rahman; M. El-Shafie; M.M. Mohammedy; Z.L. Abo-Shanab (Egyptian Journal of Petroleum)
Air blowing of asphalt generally decreases the penetration value of asphalt binder so that asphalt becomes more brittle and more susceptible to crack during thermal cycling. The aim of this study is to improve the elasticity of blown asphalt upon blending with 3%, 5%, and 7% by weight of thermoplastic waste EVA copolymer (WEVA). Physico-chemical characteristics of blended samples like (FTIR and TGA) were discussed. In addition, the physical properties including penetration test, softening point, ductility test, and elastic recovery were studied. The chemical constituents of asphalt binder including oils, resins, and asphaltenes fractions were investigated using solvent extraction technique. Also, the flow properties of dynamic viscometer at different shear rate were also measured. Moreover, the mechanical properties including storage modulus, tan δ, and stress relaxation were analyzed with dynamic mechanical analyzer at temperature range (20 °C–80 °C). The sample blended with 5%WEVA demonstrated an enhancement in storage modulus and elastic recovery and decrease in tan δ. Finally the prepared blends were applied on carbon steel panel, the paints showed an improvement in properties such as flexibility, hardness and drying times with good adhesion. The overall results approved that blending with 5 wt% (WEVA) improve the performance of blown asphalt binder. Keywords: Air blowing, Crack, Elasticity, Storage modulus, Hardness, Waste ethylene vinyle acetate copolymer (WEVA)